POLITIK HUKUM KEDUDUKAN ANAK LUAR KAWIN DALAM SISTEM HUKUM PEWARISAN DI INDONESIAÂ Â - , ERLIANTY; , Prof. Dr. Sudjito, S.H., M.Si. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This study proposed to answer some questions relating to the decision of the Constitutional Court Number 46/PUU-VIII/2010 against child born out of wedlock standing on legacy legal system in Indonesia, namely, first, about the background of the Constitutional Court No. 46/PUU-VIII/2010 publication. Second, about the process of the Constitutional Court No. 46/PUU-VIII/2010 issuance. Third, about the position of Constitutional Court's decision of law product in the legal system in Indonesia? And fourth, how Ideally Legacy Dispute Resolution Child Outside Marriage After The Constitutional Court Decision No. 46/PUU-VIII/2010? This research is a library reasearch by using four (4) types of approaches, namely conceptual, regulatory approach, a case study approach, and lastly, to approach a comparison between the concept of Islamic law with positive law. This research studied the decision, supported and enriched with library materials such as books, journals, research reports and / or secondary data relating to the decision. From this study, the authors conclude, that: first petition for judicial review filed by Machica Mochtar, who plead that Law No. 1 of 1974 on Marriage in particular Article 2 paragraph (2) providing for the registration of marriages and Article 43 paragraph (1) should be declared to have the force of law with all its consequences. Secondly, the Constitutional Court partially granted the petition for as stated in the Decision No. 46/PUU-VIII/2010. In the decision of the Constitutional Court declared the provisions of Article 43 paragraph (1) conditionally unconstitutional or constitutional conditional.Third, the decision of the Constitutional Court are final and binding (final and binding). That is, there is no chance of taking legal action following the post-verdict judgment as usual that still allow the appeal and judicial review. Fourth, the Constitutional Court's ruling does not give an explanation when there are disputants inheritance and hindered by the term \" child born out of wedlock \" Then according to the settings of the writer keeps the Civil Code (for residents who are subject to the Civil Code).